Efektivitas Video Pembelajaran Peduli Stunting Terhadap Tingkat Pengetahuan dan Keterampilan pada Kader Kesehatan - Masmuri; Nurul Hidayah; Dodik Limansyah (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
The incidence of stunting can be influenced by several factors, namely low levels of knowledge and inadequate attitudes or practices regarding the care of children with stunting. Health cadres must acquire basic information technology-based skills to help people obtain health care. This research aims to examine the effectiveness of the "Peduli Stunting" learning video on the level of knowledge and skills of cadres in the Kapuas River suburb of Pontianak City. This research method is a quantitative quasi-experiment with a pre-test and post-test approach without a control group with 50 respondents using Total Sampling and the intervensions used use learning video “peduli stunting”. The analysis results found differences in the level of knowledge and skills of cadres before and after the intervention with a significant value of 0.000 (p < 0.05). This research concludes that the learning video "Care for Stunting" increases the knowledge and skills of cadres in the Kapuas River area in the early detection of stunting. Education with the learning video "Peduli Stunting" can be applied to increase knowledge in the early detection of stunting.